2018
DOI: 10.1038/s42003-018-0161-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetically engineered human muscle transplant enhances murine host neovascularization and myogenesis

Abstract: Engineered tissues are a promising tool for addressing the growing need for tissues and organs in surgical reconstructions. Prevascularization of implanted tissues is expected to enhance survival prospects post transplantation and minimize deficiencies and/or hypoxia deeper in the tissue. Here, we fabricate a three-dimensional, prevascularized engineered muscle containing human myoblasts, genetically modified endothelial cells secreting angiopoietin 1 (ANGPT1) and genetically modified smooth muscle cells secre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 47 publications
0
24
0
Order By: Relevance
“…A previous study conducted by Koffler et al showed that 3 weeks post-implantation into abdominal wall defect, human ECs were almost completely replaced by mouse ECs and this was accompanied by a reduction in human capillary morphogenesis genes while angiogenic factors like VEGF and FGF-2 were still highly expressed [15]. In our previous studies, we used human ECs and human fibroblasts or smooth muscle cells to construct a vessel-like network within the engineered tissue that were transplanted into immunocompromised animals [8,9,15,16,18]. In the current study design, in order to transplant the engineered tissue into immunocompetent animals, we used murine ECs, SCs, and fibroblasts.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…A previous study conducted by Koffler et al showed that 3 weeks post-implantation into abdominal wall defect, human ECs were almost completely replaced by mouse ECs and this was accompanied by a reduction in human capillary morphogenesis genes while angiogenic factors like VEGF and FGF-2 were still highly expressed [15]. In our previous studies, we used human ECs and human fibroblasts or smooth muscle cells to construct a vessel-like network within the engineered tissue that were transplanted into immunocompromised animals [8,9,15,16,18]. In the current study design, in order to transplant the engineered tissue into immunocompetent animals, we used murine ECs, SCs, and fibroblasts.…”
Section: Discussionmentioning
confidence: 96%
“…We have previously reported on successful transplantation of engineered vascularized muscle tissues, constructed on PLLA/PLGA scaffolds, into an abdominal wall musculature defect in immunocompromised mice [9,15,16,18,46]. Synthetic biodegradable PLLA/PLGA scaffolds, made from polymers approved for clinical use, were shown to promote vessel formation in vitro and to enable host vessel penetration in vivo [9,13,15,18].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations